Towards an Antarctic scenarios integrated framework. Issue 1 (2nd January 2020) - Frame, Bob
ABSTRACT: The long-term future of the Antarctic is intrinsically connected to climate change and global environmental change processes driven socially and geopolitically as much as they are biophysically. The impacts and implications of these changes are increasing in global significance, including access to natural resources, biodiversity decline, and potential institutional reforms that will require much more integrated research and support to enable effective decision-making within the Antarctic Treaty System and, potentially, beyond. The 2019 Intergovernmental Panel on Climate Change (IPCC) Special Report on the Ocean and Cryosphere highlighted these issues and the importance of innovative tools and processes to increase capacity to develop appropriate policy including the need for scenario analysis. While research effort relating to Antarctica's future is increasing, there is currently no coordinated approach to establish a workable set of scenarios in which future possibilities could be actively explored. In response, this paper develops an Antarctic scenarios framework integrated with global environmental change research via an organising structure analogous to the current practice of the IPCC. It draws on Antarctic studies, climate change science and futures studies to identify a concise yet comprehensive set of 17 elements over seven categories that aim to cover all relevant social, economic and environmental factors without any weighting as to overall importance. In particular, it emphasises that biophysical research on its own is not sufficient to engage with the complex policy world which is influenced by geopolitics and, as a result, proposes a more inclusive, reflexive process. The paper then builds on the latest research on scenarios for socio-environmental analysis, modelling and decision-making to examine how this could be implemented through the integration of various components within, potentially, the Antarctic Treaty System.